Hepatic lipidomics analysis reveals the anti-obesity effects of insoluble dietary fiber from okara combined with intermittent fasting treatment in high-fat diet-fed mice - Zhao, Chenhao; Wang, Sainan; Li, Bo; Zhang, Zhao; Yu, Wei; Yu, Hansong (Frontiers in Nutrition, 2025)
IntroductionEmerging evidence has revealed that supplementation with insoluble dietary fiber (IDF) improves lipid metabolic disorders caused by a high-fat diet (HFD). Except for dietary supplementation, intermittent fasting (IF) has received widespread attention as a new dietary strategy against obesity. We hypothesized that IDF combined with IF treatment may synergistically alleviate HFD-induced lipid metabolic imbalance.MethodsThis study integrated biochemical analysis with hepatic lipidomics to explore lipid biomarkers and potential mechanisms associated with the anti-obesity effects of IDF combined with IF treatment.Results and discussionThe results indicated that IDF combined with IF treatment improved metabolic parameters associated with the obesity phenotype. Lipidomics analysis revealed that IDF combined with IF treatment altered hepatic lipid metabolic patterns in HFD-fed mice. Moreover, 15 differentially regulated lipid species were identified as lipid biomarkers. Moreover, the expression of lipogenesis-, lipid oxidation-, and cholesterol metabolism-related genes was also regulated. Our results indicate that IDF combined with IF treatment ameliorates lipid metabolism disorders in HFD-fed mice by regulating hepatic lipid metabolites and related gene expression, providing evidence for its anti-obesity effects.